2008
DOI: 10.1539/joh.l7104
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Diffuse Parenchymal Lung Diseases among Turkish Tinners

Abstract: High Prevalence of Diffuse ParenchymalLung Diseases among Turkish Tinners: Oner DIKENSOY, et al. Department of Pulmonary Diseases, Gaziantep University, Turkey-The objective is to investigate the prevalence of parenchymal lung diseases among tinners. Twenty-four tinners who signed an informed consent form in the Gaziantep area were the subjects of this study. Demographics, spirometric test results, and high resolution computed tomography (HRCT) scans were obtained for all the tinners. Out of 24 tinners, eleven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
5
1
Order By: Relevance
“…In our country, diffuse parenchymal lung diseases were detected with a ratio of 46% in Turkish tinners who were exposed to high copper concentration [2]. In our study, this ratio was detected as 56.6% higher than the other Turkish study.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…In our country, diffuse parenchymal lung diseases were detected with a ratio of 46% in Turkish tinners who were exposed to high copper concentration [2]. In our study, this ratio was detected as 56.6% higher than the other Turkish study.…”
Section: Discussioncontrasting
confidence: 63%
“…In our country, limited number of people works in the field of this ancient occupation. A study from Gaziantep-a city of Turkey-reported the radiologic findings of tinners, a similar group to coppersmiths [2]. In one study, tissue concentrations of copper in brain, lung, and kidney were significantly higher among the smelter workers than in the controls group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the measurement of trace elements may allow the better detection of airway diseases as well as give further insight into lung inflammation in diseases. In our country, diffuse parenchymal lung diseases have been detected with a ratio of 46% in Turkish illicit tinner users who were exposed to high Cu concentration [33]. In another study, this ratio was detected as being 56.6% in coppersmiths [11].…”
Section: Discussionmentioning
confidence: 62%